Factor Proportions and the Heckscher-Ohlin Theorem - Jones, R. W. (Review of Economic Studies, 1956)
Journal Article Factor Proportions and the Heckscher-Ohlin Theorem Get access R. W. Jones R. W. Jones Swarthmore, Pa. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 1–10, https://doi.org/10.2307/2296232 Published: 01 July 1956